Penelitian Kelas Oleh Guru: Konsekuensi Logis Terapan Kurikulum 1994 - Dwi Nugroho H. (Jurnal Ilmu Pendidikan, 2016)
The 1994 Curriculum makes it posible for calssroom teachers to be curriculum developers. The question is whether every teacher can develop hypothesis into research project to solve classroom problems. Classroom research is an alternative that teachers may need to be able to make professional judgement in their own classrooms. Classroom research is an activity that teachers can carry out to improve their own teaching as well as their colleagues', and to verify educational theories and assumptions relevant to classroom practices. Classroom research can start with a hypothesis about teaching on the basis of teachers' own experience